Modulation of the Pharmacological Activities of Secretory Phospholipase A2 from Crotalus durissus cascavella Induced by Naringin - Santos, Marcelo L.; Toyama, Daniela O.; Oliveira, Simone C. B.; Cotrim, Camila A.; Diz-Filho, Eduardo B. S.; Fagundes, Fabio H. R.; Soares, Veronica C. G.; Aparicio, Ricardo; Toyama, Marcos H. [UNESP] (Mdpi Ag, 2011)
In this work we have characterized the action of the naringin, a flavonoid found in grapefruit and known for its various pharmacological effects, which include antioxidant, blood lipid lowering and anticancer activity, on the structure and biochemical activities of a secretory phospholipase A (sPLA2) from Crotalus durissus cascavella, an important protein involved in the releasinge of arachidonic acid in phospholipid membranes. sPLA2 was incubated with naringin (mol:mol) at 37 degrees C and a discrete reduction in the UV scanning signal and a modification of the circular dichroism spectra were observed after treatment with naringin, suggesting modifications of the secondary structure of the protein. This flavonoid was able to decrease enzymatic activity and some pharmacological effects, such as myonecrosis, platelet aggregation, and neurotoxic activity caused by sPLA2, however, the inflammatory effect was not affected by naringin. In addition, small angle X-ray scattering (SAXS) data were collected for sPLA2 and naringin-treated sPLA2 to evaluate possible modifications of the protein structure. These structural investigations have shown that sPLA2 is an elongated dimer in solution and after treatment with naringin a conformational change in the dimeric configuration was observed. Our results suggest that structural modification may be correlated with the loss of enzymatic activity and alterations in pharmacological properties.
Keywords: secretoy phospholipase A2; Crotalus durissus cascavella; naringin; enzymatic activity pharmacological effects; small angle X-ray scattering